Effect of loading on enhancement of power performance over three consecutive trials - Robbins, D. W.; Docherty, D. (The Journal of Strength and Conditioning Research, 2005)
The acute effects of maximal voluntary isometric contractions (MVICs) in the squat position on subsequent measures of power output over 3 consecutive sets were investigated. Sixteen trained men experienced with back squats participated in the study. A 7-second MVIC was performed 4 minutes before the execution of 5 maximal countermovement jumps (CMJs) and was repeated for 3 consecutive sets (protocol 1). The results were compared to power output performance in a similar protocol (protocol 2) that excluded the 7-second MVICs. No significant differences occurred in any of the power output measurements between protocol 1 and protocol 2, nor did significance occur linearly across the 4 sets of CMJ, with the exception of a decrease in peak power in protocol 2 (p 0.05). Using both mean and maximal values only one significant correlation between either relative strength and performance enhancement or absolute strength and performance enhancement was present at p 0.01. At p 0.05, significant correlations were found between absolute strength and mean peak power (PP), mean peak acceleration (PA), mean peak force (PF), max PP, max PA, max PF, and max peak velocity. These data indicate that the execution of an MVIC performed before a power exercise was inadequate to acutely enhance power output over any of 3 consecutive trials.